2020
DOI: 10.3389/fpls.2020.00756
|View full text |Cite
|
Sign up to set email alerts
|

Role of Autophagy in Male Reproductive Processes in Land Plants

Abstract: Autophagy is a highly conserved system for degrading and recycling cytoplasmic components. The identification of autophagy-related (ATG) genes, required for autophagosome formation, has led to numerous studies using atg mutants. These studies have revealed the physiological significance of autophagy in various functions of diverse organisms. In land plants, autophagy is required for higher-order functions such as stress responses and development. Although defective autophagy does not result in any marked defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 88 publications
1
12
0
Order By: Relevance
“…Recent evidence has shown that autophagy is involved in multiple steps of sexual reproduction, depending on plant species, including male gametophyte development and maturation, self-incompatible pollen rejection and pollen germination (Harrison-Lowe and Olsen, 2008; Kurusu et al, 2014; Li et al, 2020; Norizuki et al, 2020; Zhao et al, 2020; Zhou et al, 2021; Macgregor et al, 2022). Nevertheless, the role(s) of canonical autophagy during sexual reproduction in Arabidopsis thaliana is still an enigma since almost all of the autophagy-defective Arabidopsis mutants such as atg2 , atg5 and atg7 exhibit normal life cycles without any deleterious phenotypes during fertilization, embryogenesis and seed formation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has shown that autophagy is involved in multiple steps of sexual reproduction, depending on plant species, including male gametophyte development and maturation, self-incompatible pollen rejection and pollen germination (Harrison-Lowe and Olsen, 2008; Kurusu et al, 2014; Li et al, 2020; Norizuki et al, 2020; Zhao et al, 2020; Zhou et al, 2021; Macgregor et al, 2022). Nevertheless, the role(s) of canonical autophagy during sexual reproduction in Arabidopsis thaliana is still an enigma since almost all of the autophagy-defective Arabidopsis mutants such as atg2 , atg5 and atg7 exhibit normal life cycles without any deleterious phenotypes during fertilization, embryogenesis and seed formation.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to low temperature promotes the degradation of CO by the HOS1-dependent proteasome and leads to FT inhibition, thereby delaying flowering [ 117 , 118 ]. Autophagy is also required in the tapetal PCD during the development and maturation of pollen, and participates in plant responses to abiotic stresses [ 119 , 120 ]. Moreover, autophagy is also involved in the breakdown of liposomes and the transfer of lipids from tapetum cells to the surface of microspores in rice [ 121 ].…”
Section: The Protective Mechanism Of Antioxidant In Pollen Developmen...mentioning
confidence: 99%
“…Autophagy is involved in male gametogenesis in mammals and bryophytes (Norizuki et al, 2020), but their roles seem to diverge. Mice defective in autophagy exhibit defects in the reorganization of microtubules and organelles, and similar effects have also been reported in the moss P. patens (Huang et al, 2021;Sanchez-Vera et al, 2017;Shang et al, 2016;Wang et al, 2014).…”
Section: Multiple Degradation Systems Mediate Spermiogenesis In M Pol...mentioning
confidence: 99%